INTERACTIVE ONLINE ASSESSMENT WITH MySQL: DEVELOPMENT AND APPLICATION IN THE EDUCATIONAL PROCESS - Головач, Йожеф (SWorldJournal, 2025)
The article considers issues related to the organization of the educational process for studying database management systems, in particular MySQL. On the basis of modern information technologies, it has become possible to develop new-generation textbooks.